Evaluation of neurological and cardiac development of newborn infants born to mothers infected with COVID-19: Does COVID-19 affect the development of newborn infants? - Ayar, Murat; Gazeteci Tekin, Hande; Sevinç, Yeliz; Öztekin, Deniz; Olukman, Özgür (Journal of Surgery and Medicine, 2022)
Background/Aim: In the coronavirus disease 2019 (COVID-19) pandemic, which has been affecting the world for the last 2 years, pulmonary, cardiovascular, and neurological adverse effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported. These negative influences entail a risk for fetal progress. In this study, by performing a detailed clinical evaluation, postnatal ultrasonography, and echocardiography, we aimed to investigate potential neurological and cardiac complications of newborns born to pregnant women infected with COVID-19. Methods: This prospective and cross-sectional study was conducted between January and July 2021. Newborn infants (0–28 days postpartum) born to mothers with proven COVID-19 infection by positive RT-PCR test during pregnancy were enrolled. Fetal cardiac development was evaluated by a pediatric cardiologist with an echocardiographic examination. Fetal neurologic evaluation was performed by a pediatric neurologist using both neurologic examination and transfontanelle ultrasonography (TFUS). Infants were reevaluated every 2 months until 6 months of age. Results: Thirty-three female and 32 male infants born to 64 pregnant women, one being a twin birth, were included in the study. Seven women developed COVID-19 infection in the first trimester, 11 in the second trimester, and 46 in the third trimester. Neurological examination and TFUS were normal in all newborns except one with microcephaly. The etiologic cause could not be detected in this infant, and his neurodevelopment was normal in the follow-up. The cardiac examination did not reveal any significant disorders. Eleven infants failed the standard “Auditory Brainstem Response” (ABR) hearing screening test, so a second test was performed. Only two infants required further investigation after the second test. Conclusion: We did not observe any neurologic and cardiologic teratogenic effects associated with COVID-19 infection during pregnancy.